2004
DOI: 10.1097/01.brs.0000129895.90939.1e
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Expandable Cages for Vertebral Body Replacement in the Thoracolumbar Spine

Abstract: Biomechanical results indicate that design variations of expandable cages for vertebral body replacement are of little importance. Additionally, no significant difference could be determined between the biomechanical properties of expandable and nonexpandable cages. After corporectomy, isolated implantation of expandable cages plus anterior plating was not able to restore normal stability of the motion segment. Therefore, isolated anterior stabilization using cages plus Locking Compression Plate should not be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
63
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 20 publications
13
63
0
5
Order By: Relevance
“…Despite these different implant features and material properties the results of the present study demonstrated only minimal differences in the postimplantational stability between expandable and nonexpandable VBRs. Similar results have been shown for rather more stable corpectomy models [31,43] and indeed, for the defect situation after en bloc resections [38], we also were not able to reveal an advantage of the expandability of an VBR. However, it seems conceivable that expandability of a VBR implant may decrease secondary VBR dislocation [21,30].…”
Section: Influence Of Vbr Designsupporting
confidence: 90%
See 3 more Smart Citations
“…Despite these different implant features and material properties the results of the present study demonstrated only minimal differences in the postimplantational stability between expandable and nonexpandable VBRs. Similar results have been shown for rather more stable corpectomy models [31,43] and indeed, for the defect situation after en bloc resections [38], we also were not able to reveal an advantage of the expandability of an VBR. However, it seems conceivable that expandability of a VBR implant may decrease secondary VBR dislocation [21,30].…”
Section: Influence Of Vbr Designsupporting
confidence: 90%
“…This finding may reflect the fact that the protective effect of additional antero-lateral angular stable plating on short posterior fixation is masked by the primary stabilizing effect of a long posterior construct. Thus, the biomechanical advantage of an optional anterior plate fixation in previous studies needs to be seen differentially as it may depend on the length of posterior fixation [43,63]. However, a simple comparison of the results obtained in the present en bloc spondylectomy study with corpectomy studies seems not appropriative [28].…”
Section: Influence Of Posterior Fixation Lengthmentioning
confidence: 85%
See 2 more Smart Citations
“…However, isolated posterior instrumentations are often accompanied by complications like a loss of correction or implant failure. Therefore, especially in thoracolumbar burst fractures, an anterior approach for reconstruction and stabilization of the anterior vertebral column is often necessary to restore regular spinal column loading [3,10,15,17,25,26,32,33]. Additional anterior approaches to the spine and the 360°fusion are also reasonable from the biomechanical point of view: different biomechanical studies, dealing with a total corpectomy defect model to simulate a rotationally instable fracture, reported the highest stiffness in all motion planes for this kind of fractures treated with 360°fusion [15,17,25].…”
Section: Introductionmentioning
confidence: 99%